2016
DOI: 10.1021/acs.jproteome.6b00002
|View full text |Cite
|
Sign up to set email alerts
|

Soft Corals Biodiversity in the Egyptian Red Sea: A Comparative MS and NMR Metabolomics Approach of Wild and Aquarium Grown Species

Abstract: Marine life has developed unique metabolic and physiologic capabilities and advanced symbiotic relationships to survive in the varied and complex marine ecosystems. Herein, metabolite composition of the soft coral genus Sarcophyton was profiled with respect to its species and different habitats along the coastal Egyptian Red Sea via (1)H NMR and ultra performance liquid chromatography-mass spectrometry (UPLC-MS) large-scale metabolomics analyses. The current study extends the application of comparative seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 57 publications
(110 reference statements)
6
71
1
Order By: Relevance
“…91 A total of 120 metabolites including 65 diterpenes, 8 sesquiterpenes, 18 sterols, and 15 oxylipids were identified. A number of these contributed to the differentiation of species and their unique habitats.…”
Section: Combining Nmr and Msmentioning
confidence: 99%
“…91 A total of 120 metabolites including 65 diterpenes, 8 sesquiterpenes, 18 sterols, and 15 oxylipids were identified. A number of these contributed to the differentiation of species and their unique habitats.…”
Section: Combining Nmr and Msmentioning
confidence: 99%
“…The content of cembranoid is highly dependent upon environmental factors, as the ecological relationship with the number of predators and spatial competitors (Slattery, Starmer, & Paul, 2001). Soft coral that was taken from natural coral reefs was detected to contain diverse cembranoid compounds than cultivated aquariums (Farag et al, 2016). Our previous finding also showed cembranoid was produced in higher concentration at healthier coral reef environment (Januar, Hendrarto, Chasanah, & Wright, 2011;Januar, Marraskuranto, Patantis, & Chasanah, 2012;Januar et al, 2015).…”
Section: Introductionmentioning
confidence: 61%
“…Meanwhile, cembranoid content also depends on the genetic diversity of soft coral. Previous studies on Sarcophyton glaucum found that each genetic clade (Clade A to F) contains a combination of 8 cembranoid chemotypes (Aratake et al, 2012;Farag et al, 2016). Furthermore, multivariate statistics for cembranoid quantity was successfully validated to be a profiling taxonomic approach between soft coral Lobophytum, Sinularia, and Sarcophyton (Farag et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
“…Examination of the loading plot indicated that the distant clustering of ZnCl 2 and SA elicited coral samples was almost exclusively due to mass signals m/z 361, 383 and 743 eluted at retention time ( R t ) 5.32 corresponding to sarcophytonolide I and assigned as [M + H] + , [M + Na] + and [2 M + Na] + , respectively. Details on metabolites identification strategy has previously been published 38 . Hierarchical cluster analysis, similar to PCA, is an unsupervised data analysis method that establishes relationships among similar groups of samples allowing for analysis of the results in a fairly easier way.…”
Section: Resultsmentioning
confidence: 99%
“…Although different Sarcophyton species were subjected to extensive chemical and biological studies 38 , to our knowledge there are no reports regarding the chemical composition of the corals in response to elicitation using large scale untargeted analytical techniques. Metabolomics, defined as the comprehensive profiling of all metabolites within a given sample in a particular physiological state, provide a holistic measure of the global changes occurring post elicitation.…”
Section: Introductionmentioning
confidence: 99%